Exercise oscillatory ventilation: Mechanisms and prognostic significance - Dhakal, Bishnu P (World J Cardiol, 2016)
Alteration in breathing patterns characterized by cyclic variation of ventilation during rest and during exercise has been recognized in patients with advanced heart failure (HF) for nearly two centuries. Periodic breathing (PB) during exercise is known as exercise oscillatory ventilation (EOV) and is characterized by the periods of hyperpnea and hypopnea without interposed apnea. EOV is a non-invasive parameter detected during submaximal cardiopulmonary exercise testing. Presence of EOV during exercise in HF patients indicates significant impairment in resting and exercise hemodynamic parameters. EOV is also an independent risk factor for poor prognosis in HF patients both with reduced and preserved ejection fraction irrespective of other gas exchange variables. Circulatory delay, increased chemosensitivity, pulmonary congestion and increased ergoreflex signaling have been proposed as the mechanisms underlying the generation of EOV in HF patients. There is no proven treatment of EOV but its reversal has been noted with phosphodiesterase inhibitors, exercise training and acetazolamide in relatively small studies. In this review, we discuss the mechanistic basis of PB during exercise and the clinical implications of recognizing PB patterns in patients with HF.